Anúncio Publicitário em sala de aula do ensino médio: uma proposta de sequência didática para compreensão leitora - Otero, Renata marques de (2016)
Faced with the undeniable presence of advertising stimuli in everyday life of the population and exposure of adolescents to announcements of all kinds, it is very important that the school works this genre in Portuguese classes. For the preparation of this research, we assume that knowing concepts with which handles advertising daily, and ad writing techniques, high school students will expand their ability to read and understand this genre, an essential condition for evaluate it critically and be able to position themselves consciously against this type of message they are exposed constantly. Thus we have as a general objective to discuss the results of an intervention made by a reading teaching proposal of the advertisement genre for high school students, from a didactic sequence based on reading comprehension strategies. At first, we made a theoretical reflection, divided into three parts. In the first, we study reading conception, prior knowledge and reading strategies present in Koch and Elias (2012), Kleiman (2013) and Solé (1998); in the second, we deal with the question of genre, based on Marcuschi (2008), followed by the specific part with respect to advertising and advertising text, for which we seek support in Carvalho (1998), Martins (2003), Sant 'Anna (1998) and Sampaio (2003), and know the treatment that is devoted to advertising in Brasil and Pernambuco official documents relating to teaching Portuguese, specifically, the PCN and PCN+ de Língua Portuguesa para o Ensino Médio (2000) and the Parâmetros para a Educação Básica do Estado de Pernambuco – Língua Portuguesa (2012); in the third part, we turn to Schneuwly and Dolz (2010), and consult the Orientações Teórico-Metodológicas para o Ensino Médio – Língua Portuguesa (PE) (2011), the Base Curricular Comum para as Redes Públicas de Ensino de Pernambuco – Língua Portuguesa (2008) and the Currículo de Português para o Ensino Médio (PE), which offered the methodological approaches to the implementation of the proposal in the classroom. In the following chapter, we present the survey results, containing the analysis of a semi-structured interview, conducted in the form of focus group with five students of the 2nd Year of a Escola de Referência em Ensino Médio, in São Lourenco da Mata, as well as a didactic sequence that was applied to a class of 45 students throughout the process. The ads used in the lessons were chosen from Pernambuco newspapers the months May to August 2015. As a result, we saw that it was possible to increase the level of reading and understanding about the ads, with special emphasis on the development of the ability to make inferences, which contributed to the development of other important skills for reading texts.